2014
DOI: 10.1007/s00432-014-1888-8
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate transporter 4 predicts poor prognosis in hepatocellular carcinoma and is associated with cell proliferation and migration

Abstract: MCT4 expression can predict survival and TACE treatment response for HCC patients. Furthermore, MCT4 plays an important role in HCC cell proliferation, migration, and invasion. The inhibition of MCT4 can induce inactivation of HIF-1α and inhibit phosphorylation of AKT. MCT4 may be a potential therapeutic target for the treatment of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 28 publications
3
43
0
Order By: Relevance
“…34 The lactate exporter MCT4, which is overexpressed in glycolytic tumor cells, is a promising candidate for cancer prognosis in various cancer entities, such as pancreatic cancer, 35 clear cell renal cell carcinoma, 29 or hepatocellular carcinoma. 36 A recent meta-analysis corroborates that increased MCT4 expression is linked to poor patient outcome across five different cancer entities. 37…”
Section: Wwwcts-journalcommentioning
confidence: 86%
See 1 more Smart Citation
“…34 The lactate exporter MCT4, which is overexpressed in glycolytic tumor cells, is a promising candidate for cancer prognosis in various cancer entities, such as pancreatic cancer, 35 clear cell renal cell carcinoma, 29 or hepatocellular carcinoma. 36 A recent meta-analysis corroborates that increased MCT4 expression is linked to poor patient outcome across five different cancer entities. 37…”
Section: Wwwcts-journalcommentioning
confidence: 86%
“…In prostate cancer, MCT2 has been proposed as a biomarker for disease diagnosis, because the transporter is not expressed in normal prostate tissue, an increase in expression can be observed in adjacent non‐neoplastic tissue and strong MCT2 expression is found in primary prostate tumor tissue samples 34. The lactate exporter MCT4, which is overexpressed in glycolytic tumor cells, is a promising candidate for cancer prognosis in various cancer entities, such as pancreatic cancer,35 clear cell renal cell carcinoma,29 or hepatocellular carcinoma 36. A recent meta‐analysis corroborates that increased MCT4 expression is linked to poor patient outcome across five different cancer entities 37…”
Section: Mcts In Cancermentioning
confidence: 99%
“…The role of over-expressed MCT4 in HCC has been illustrated. It is associated with HCC progression and poor prognosis[48,49]. The latest study observed the reduced expression of MCT1 and MCT2 in HCC[50].…”
Section: Reprogramming Of Glucose Metabolism-related Enzymes and Tranmentioning
confidence: 99%
“…Monocarboxylic acid transporter 4 (SLC16A3/MCT4) is one of the membrane protein stubs in cells that is structurally able to output lactic and pyruvic acids and affect the acidity of the tumor microenvironments. [15][16][17] High expression of MCT4 has been reported to be a biomarker in various types of tumors, [18][19][20][21][22][23][24] which makes it an appealing therapeutic target in cancers. The blockade of MCT4 expression has been shown to represent a novel treatment target in glioblastoma, large B-cell lymphoma, and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%